2019
DOI: 10.3390/ijms20246112
|View full text |Cite
|
Sign up to set email alerts
|

Lercanidipine Synergistically Enhances Bortezomib Cytotoxicity in Cancer Cells via Enhanced Endoplasmic Reticulum Stress and Mitochondrial Ca2+ Overload

Abstract: The proteasome inhibitor (PI), bortezomib (Btz), is effective in treating multiple myeloma and mantle cell lymphoma, but not solid tumors. In this study, we show for the first time that lercanidipine (Ler), an antihypertensive drug, enhances the cytotoxicity of various PIs, including Btz, carfilzomib, and ixazomib, in many solid tumor cell lines by inducing paraptosis, which is accompanied by severe vacuolation derived from the endoplasmic reticulum (ER) and mitochondria. We found that Ler potentiates Btz-medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…During this process, they disrupt Ca 2+ homeostasis at the ER by altering Ca 2+ store content and Ca 2+ dynamics (including the uptake, release, and leakage of Ca 2+ ) and/or at the mitochondria by affecting the activities of MCU complex components to regulate the mitochondrial Ca 2+ levels. In addition, recent studies have shown that treatment of cancer cells with drugs that perturb Ca 2+ homeostasis [CGP-37157 ( Yoon et al, 2012 ), lercanidipine ( Lee et al, 2019 ), and loperamide ( Kim et al, 2019 )] or Nutlin-3, which is a chemical that triggers the mitochondrial unfolded protein response (mtUPR) ( Lee et al, 2017 ), induces paraptosis when combined with proteasome inhibitors (PIs). The proposed targets through which these paraptosis-inducing agents disrupt Ca 2+ homeostasis are summarized in Figure 1 .…”
Section: Paraptosis-inducing Agents Associated With Ca 2+ mentioning
confidence: 99%
See 4 more Smart Citations
“…During this process, they disrupt Ca 2+ homeostasis at the ER by altering Ca 2+ store content and Ca 2+ dynamics (including the uptake, release, and leakage of Ca 2+ ) and/or at the mitochondria by affecting the activities of MCU complex components to regulate the mitochondrial Ca 2+ levels. In addition, recent studies have shown that treatment of cancer cells with drugs that perturb Ca 2+ homeostasis [CGP-37157 ( Yoon et al, 2012 ), lercanidipine ( Lee et al, 2019 ), and loperamide ( Kim et al, 2019 )] or Nutlin-3, which is a chemical that triggers the mitochondrial unfolded protein response (mtUPR) ( Lee et al, 2017 ), induces paraptosis when combined with proteasome inhibitors (PIs). The proposed targets through which these paraptosis-inducing agents disrupt Ca 2+ homeostasis are summarized in Figure 1 .…”
Section: Paraptosis-inducing Agents Associated With Ca 2+ mentioning
confidence: 99%
“…A recent study showed that lercanidipine (Ler), a third-generation 1,4-dihydropyridine (DHP) used to treat high blood pressure, potentiates the antitumor effects of various PIs (e.g., Btz, carfilzomib, and ixazomib) in many solid cancer cell lines by inducing paraptosis, a cell death mode accompanied by extensive vacuolation derived from the ER and the mitochondria ( Lee et al, 2019 ). Ler enhances Btz-mediated ER stress and ER dilation in MDA-MB 435S cells.…”
Section: Paraptosis-inducing Agents Associated With Ca 2+ mentioning
confidence: 99%
See 3 more Smart Citations